A pesquisa como recurso da formação e da construção de uma nova identidade docente: notas para uma discussão inicial - Isauro Beltrán Nuñez; Betania Leite Ramalho (EccoS – Revista Científica)
This article treats research as a component of the professional teaching identity. It advocates a need for the formation of teaching research attitudes connected with the construction of a new professionalism and new personal and professional identities. Identity becomes a structuralizing category for the new professional action, in which research makes for one of its components. It also analyzes the learnings and the settings that contribute for the configuration of the identities, especially the initial formation and school, being the last considered as the focus of the continuing formation and professional development. Such theme has been subject of studies for the Grupo Formação e Profissionalização Docente do Programa de Pós-Graduação em Educação, da Universidade Federal do Rio Grande do Norte (UFRN), created in 1995 and coordinated by the authors of this article